THE EXTRA-LEGAL PROPERTY RIGHTS DESIGN OF BITCOIN AND ITS PHILOSOPHICAL ISSUES - Nur Fauzan, M. Pasha; Yoppy A, Muhammad (Bank Indonesia, 2022)
This article provides a philosophical examination of the Bitcoin concept of property rights protection. To that end, several fundamental questions must be addressed on the subject, including what money is, what purpose it seeks to serve, and how the system that supports it is related to the concept of property rights. Finally, it is important to identity what, if anything, Bitcoin has to offer in these matters. This article concludes that the primary function of money as a social institution is to store one’s labour as part of one’s property right. In comparison to fiat currency, Bitcoin is the superior medium of exchange. However, the ideological foundation of Bitcoin has philosophical issues: it is based on the false premises of absolute individual property rights derived from the concept of natural rights, which is incompatible with Indonesia’s economic commitment and goals of establishing a welfare state, as reflected in the constitution.